(untitled) (Superficies y Vacío, 2017)
Dental caries is an infectious disease that can occur in children, sometimes as soon as the teeth eruption starts. Nanotechnology provides effective strategies in prevention and treatment of dental caries. The purpose of this study was to determine the effectiveness of the addition of silver nanoparticles to a fluoride varnish for the remineralization of primary teeth with white spot lesions. A trial was carried out in children with dental demineralization (white spot lesions) on both maxillary dental teeth. One of the teeth received three applications of a fluoride varnish with silver nanoparticles, and the other one, three applications of the same varnish without the silver nanoparticles. We measured the mineral content of the teeth with a laser cavity detection device (DIAGNOdent®) before the first application of the varnishes, and 3 months after the last application. The results show significant differences between teeth treated with silver nanoparticles. Teeth have been treated with fluoride varnish added with silver nanoparticles seemed to enhance dental structure than teeth treated with conventional varnish, and this effect was also found between basal and final measurements in this group. The fluoride varnish added with silver nanoparticles seems to be more effective in the dental remineralization. This strategy may be used as a prophylactic measure to avoid development of caries.